Systematics and biogeography of Mesobola brevianalis (Boulenger, 1908) (Teleostei: Cyprinidae) - Riddin, Megan Amy (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2015)
The accurate identification of fish species, their life stages and their products enables the correct management of fisheries, research and conservation of distinctive populations for long-term survival and sustainability. Mesobola brevianalis Boulenger, 1908, commonly known as the river sardine, is found in many river systems in southern Africa. Because it exhibits widely separated populations showing subtle differences, particularly in colour, it is thought that there may be cryptic species involved. Standard phylogenetic techniques using three genetic markers (mitochondrial COI, nuclear protein RAG1 and nuclear ribosomal 28S rRNA), enabled the building of phylogenetic networks for M. brevianalis and some outgroup species. Consistent patterns of relationship were seen with 28S supporting monophyly. COI and RAG1 suggested that populations that are currently identified as M. brevianalis in fact represent several species. There was sufficiently strong support for the evolutionary independence of the M. brevianalis populations from the Rovuma, Kunene and Orange River Systems to consider them as independent species. The independence of the genus Mesobola was brought into question because Engraulicypris sardella and Rastrineobola argentea were placed within it phylogenetically.Morphometric methods in the form of multivariate truss network analyses, were performed to locate morphological markers for populations. There was little to no variation among most of the populations synonymized under M. brevianalis. Furthermore, neither latitude nor longitude had an effect on the morphological characters that might be linked to functional evolution. A molecular clock analysis of COI data was used to calibrate a paleobiogeographical model which entailed a divergence of lineages starting from an easterly reigning Paleo-Congo Basin, via a hypothetical Paleo-Kalahari Lake that was fragmented by a series of uplifts and drying events beginning ~65 million years ago. Complete evidence supported the synonymisation of the genera Engraulicypris and Mesobola, the resurrection of the species name gariepinus for the Orange River Systempopulation, and the description of two new species: E. ngalala from the Rovuma River System and E. howesi from the Kunene River System.
Keywords: River sardine Morphology; Molecular evolution; Biogeography; Phylogenetic network; River sardine -- South Africa; Paleobiogeography